Spatial and Temporal Coupling Coordination and Influencing Factors of Digital Inclusive Finance and Ecological Civilization Construction in China - Zhou, Chuhan (Transactions on Economics, Business and Management Research, 2023)
This paper uses the spatial coupled coordination model, spatial autocorrelation analysis and spatial Durbin model to explore the spatio-temporal pattern and influencing factors of the coupled coordination index between ecological civilization construction (ECC) and digital finance (DF). The results show that: (1) From 2011 to 2021, the coupling coordination degree between ECC and DF in China shows an increasing trend. Besides, the degree of coupling coordination has obvious spatial diversity. The eastern provinces are generally larger than the western provinces, and this pattern is relatively stable. (2) The coupling degree between neighboring provinces and cities has a strong positive correlation, and it is growing every year recently. (3) The test results of spatial Durbin model show that the human capital, economic growth, technological innovation and trade factors can help coupling coordination to raise. cities development and industrial structure have negative effects on coupling coordination.